Distributed containment control of fractional-order uncertain multi-agent systems. Issue 7 (May 2016) - Chen, Jie; Guan, Zhi-Hong; Yang, Chao; Li, Tao; He, Ding-Xin; Zhang, Xian-He
Abstract: This paper investigates the containment control problem of uncertain linear multi-agent systems, where the dynamics of each agent is described by a fractional-order differential equation. Based on the stability theory of fractional-order systems and matrix theory, some sufficient conditions are presented to ensure that the states of the followers can asymptotically converge to the convex hull formed by those of the leaders, and the feedback matrix of the proposed protocol is also determined according to linear matrix inequalities. Two simulation examples are provided to demonstrate the effectiveness of the theoretical results.